Targeted Mutational Profiling Reveals Clonal Relationships in Metachronous Occurrence of Classic Hodgkin and Mediastinal Large B-Cell Lymphomas. (25th January 2023) - Singh, Kunwar; Lezama, Lhara S.; Kurzer, Jason; Oak, Jean; Schultz, Liora M.; Walkush, Ann; Cheng, Tse-Chang; Chen, Everett H.; May, William A.; Chang, Cheryl; Link, Michael P.; Advani, Ranjana H.; et al.
Abstract : Classic Hodgkin lymphoma (CHL) patients may infrequently present with a prior or recurrent disease with discordant histology resembling non-Hodgkin lymphomas. These include primary mediastinal large B-cell lymphoma (PMBL), diffuse large B-cell lymphoma (DLBCL), or mediastinal gray-zone lymphoma (MGZL). Such patients are often refractory to standard therapy and their diagnosis is hampered by significant morphologic and immunophenotypic overlap and insufficient molecular data. Among 509 CHL patients seen at an academic medical center, 6 patients had a prior or subsequent diagnosis different from CHL. Paired tissue samples were evaluated by targeted mutational analysis using a 164-gene panel. Our findings show multiple shared variants indicative of a clonal relationship between the CHL and the PMBL, DLBCL, or MGZL diagnoses. Most frequent mutated genes included TNFAIP3 (4 of 6, 66.7%), STAT6 (3 or 6, 50%), ARID1A (3 of 6, 50%), and XPO1 (3 of 5, 60%). Three patients showed the same oncogenic variant within the XPO1 gene (E571K), and mutations in TNFAIP3 and B2M were observed in 2 of the 5 patients with shared variants. In addition, differences in the mutation profile between the lymphoma pairs were also observed, which could represent clonal evolution. Mutational profiling could be of benefit in patients with recurrent/refractory disease with discordant histology, where the clonal relationship could be helpful to inform and guide therapeutic decisions. These findings provide further evidence of a true biological continuum surrounding CHL, PMBL, DLBCL, and MGZL and shed light on underlying genetic events and their clinical impact.